An Interpretation of the Qur’an, Surat At-Talaq, 65:12: Analysis from the Qur’an, Ahadith and Signs in the Field of Astronomy and Geology - Kitota, Abdillah (Journal of Quranic Sciences and Research, 2023)
There is difference of opinions among Muslim scholars regarding whether Allah (S.W.T) has created one Earth or seven separate earths or many earths. The objective of this study was to analyze the kawniyyat verses related to creation of heavens and Earth; to show which opinion among the three is likely to be correct. This study has used Thematic Approach and Synoptic Approach in reviewing and analysing the kawniyyat verses related to the creation of heavens and Earth; in relation to the modern signs in the field of Astronomy and Geology. Qur’anic and ahadith data were collected from the tafsir of the Qur’an and ahadith books. The Astronomical and Geological data were screened from online databases. The findings show that Allah (S.W.T) has created one Earth with seven concentric layers inside it.These findings may rekindle the interest of other scholars to mount further research in this subject.